The Phrenological journal and science of health ... incorporated with the Phrenological magazine ... Devoted to ethnology, physiology, phrenology, physiognomy, sociology, psychology, education, mechanical industry, hygiene, and to all those progressive measures which are calculated to reform, elevate, and improve mankind, spiritually, intellectually, and socially. - Allen, Nathan 1813-1889.; Beall, Edgar Charles 1853-.; Drayton, Henry Shipman 1840-.; Fowler, Lorenzo Niles 1811-1896.; Fowler, Orson Squire 1809-1887.; Sizer, Nelson 1812-1897.; Wells, Samuel Robert 1820-1875. ([New York O.s. & L.N. Fowler, 1838)
Monthly.
Absorbed Life illustrated in May 1861; Packard's monthly in Apr. 1870; Science of health in July 1876; the Phrenological magazine (London) in Jan. 1897.
Apr.-Dec. 1870, The Phrenological journal and Packard's monthly.
Editors: 1838-41, Nathan Allen.--1841- O.S. Fowler (with L.N. Fowler, 1849- ).--18 Nelson Sizer. --18- -75, S.R. Wells, Nelson Sizer. --1875-84, H.S. Drayton, Nelson Sizer.--1885- H.S. Drayton. --18 E.C. Beall.
Jan. 1851- American phrenological journal, and repository of science, literature and general intelligence.
Jan.1871-Dec. 1884, The Phrenological journal and life illustrated. (Cover title, July 1876-Dec. 1884: The Phrenological journal and science of health ; t.p. and caption title read: The Phrenological journal and life illustrated)
Jan.1885-19 The Phrenological journal and science of health (subtitle varies)
Keywords: Phrenology -- Periodicals